Otimização do teste de vazamento em unidades evaporadas no processo de produção de condicionadores de ar - CORRÊA, Daniel Amorim (Universidade Federal do Pará, 2021)
The manufacture of air conditioners requires a detailed inspection of its manufacturing processes due to the risk it presents. One of the most significant risks and which the research proposes to address, refers to the loss of refrigerant fluid to the environment, as well as actions that can solve the impact of this leak on the production process and on the final customer. This type of problem causes great damage to the product, due to the loss of refrigerant gas and the environment due to the significant impact on the increase of the greenhouse effect. The objective is to carry out effective combat by creating an automation system capable of detecting leaks in condensing units and enabling immediate intervention, aiming to reduce the impacts resulting from an accident, contributing significantly to the quality of the finished product. The work has some significant points such as, firstly, sections of an introductory and organizational nature where it is intended to present the scope, objectives and structure of the dissertation. Subsequently, the history of air conditioning is discussed, as well as the definitions and tools adopted. Then, the actual situation in approach to the physical problem and the details of the current state. As a result, as a result, the impact on reducing operator health risk and increasing productivity.